Leading within systems of inequity in education : a liberation guide for leaders of color - Rice-Boothe, Mary (ASCD, 2023)
"This indispensable liberation guide will help leaders of color overcome obstacles and create the path to genuine equity in schools"-- Provided by publisher.
Keywords: Minority school administrators -- United States.; School management and organization -- Vocational guidance -- United States.; Racial justice in education -- United States.; Educational leadership -- United States.; Educational equalization -- United States.; Administrateurs scolaires issus des minorités -- États-Unis.; Administration scolaire -- Orientation professionnelle -- États-Unis.; Leadership en éducation -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; Educational equalization; Educational leadership; Minority school administrators; Racial justice in education; School management and organization -- Vocational guidance; United States